2015
DOI: 10.1002/cctc.201500394
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CO Oxidation on the Oxide/Metal Interface: From Ultra‐High Vacuum to Near‐Atmospheric Pressures

Abstract: Abstract. We studied CO oxidation on FeO(111) films on Pt(111) at sub-monolayer oxide coverages at ultra-high vacuum (UHV) and near-atmospheric pressure conditions. The FeO (111) bilayer islands are inert towards CO2 formation. In contrast, the FeO2-x trilayer structure shows substantial CO2 production that reaches a maximum at(~40%) coverage at both, UHV and realistic, pressure conditions. The results provide compelling evidence that the FeO2-x/Pt (111) interface is the most active in CO oxidation. Although F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 38 publications
7
59
0
Order By: Relevance
“…This is a scenario compatible with DFT calculations 265 for periodic structures, which revealed the lowest oxygen binding energy at the intrinsic FeO/FeO 2Àx interface. If the iron oxide islands are exposed to mixtures of CO and oxygen, STM images basically corroborate the previous observation that CO/O 2 mixtures with excess CO reduce the islands and excess oxygen prevents excess reduction.…”
Section: Strong Metal Support Interaction (Smsi)supporting
confidence: 87%
See 1 more Smart Citation
“…This is a scenario compatible with DFT calculations 265 for periodic structures, which revealed the lowest oxygen binding energy at the intrinsic FeO/FeO 2Àx interface. If the iron oxide islands are exposed to mixtures of CO and oxygen, STM images basically corroborate the previous observation that CO/O 2 mixtures with excess CO reduce the islands and excess oxygen prevents excess reduction.…”
Section: Strong Metal Support Interaction (Smsi)supporting
confidence: 87%
“…In order to evaluate the influence of the open oxide-Pt interface, studies on partially covered Pt single crystals at near atmospheric pressure were performed. 265 Indeed, the results indicated that the Pt-oxide interface is more reactive than the fully covered film. [266][267][268][269][270][271] Therefore, until recently, there has been evidence that the open oxide-metal interface (in the spirit of an inverse catalyst: see Section 3.2) is the active site.…”
Section: Strong Metal Support Interaction (Smsi)mentioning
confidence: 98%
“…It is important to note that asimilar picture has previously been observed by STM on continuous FeO 2Àx films on Pt(111) treated in the mbar pressure range,w here compact domains of FeO 2Àx were surrounded by areas formed upon reduction with CO. [15] It has been proposed that the reduction process starts on some defects.I nt he case of partially covered films, the transformation is definitely triggered at the island edges via reaction with CO adsorbed on Pt. Certain similarities between the results on dense FeOf ilms at high pressures [15] and those obtained in this study for FeOi slands at low pressures,suggest that the reaction in both cases occurs at the interface between the reduced (red) and the oxidized (ox) phases of the film formed under reaction conditions,t hat is, on the oxide red /oxide ox interface,i rrespectively of the film coverage.T he observed coverage effect [10] may be linked to the easy formation of the reduced phase via reaction between CO adsorbed on Pt and oxygen at the oxide island edge in partially covered films.T herefore,P tm ay be considered as ap romoter for the formation of the active interface rather than directly participating in the catalytic reaction.…”
Section: Angewandte Chemiementioning
confidence: 96%
“…[8] Although this mechanism may be operative under UHVbased conditions,ithardly holds true at the realistic pressures, which force the formation of the FeO 2Àx phase.I ndeed, the transformation of ad ense FeOf ilm into FeO 2Àx sets in at O 2 pressures as low as 10 À2 mbar at 300 K [4] and even in 10 À6 mbar O 2 at about 600 Kf or FeOislands. [9] Pan et al [10] studied CO oxidation on the FeO(111)/ Pt(111) films at near atmospheric pressures as af unction of the film coverage.T he activity vs.c overage plot showed am aximum at about 0.4 ML, indicating that the oxide/metal boundary is more active than the film surface itself.F urthermore,t emperature-programmed reaction experiments only showed CO 2 production on oxidized FeO 2Àx films,w ith am aximum reached at nearly the same coverage.A ll these results provided strong evidence that it is the FeO 2Àx /Pt interface that catalyzes the reaction under realistic conditions. Accordingly,t he enhanced reactivity was attributed to the reaction between CO adsorbed on Pt and oxygen species at the FeO 2 edges.…”
mentioning
confidence: 99%
See 1 more Smart Citation